Cloning of human papilloma virus genomic DNAs and analysis of homologous polynucleotide sequences. - Heilman, C A (1980)
The complete DNA genomes of four distinct human papilloma viruses (human papilloma virus subtype 1a [HPV-1a], HPV-1b, HPV-2a, and HPV-4) were molecularly cloned in Escherichia coli, using the certified plasmid vector pBR322. The restriction endonuclease patterns of the cloned HPV-1a and HPV-1b DNAs were similar to those already published for uncloned DNAs. Physical maps were constructed for HPV-2a DNA and HPV-4 DNA, since these viral DNAs had not been previously mapped. By using the cloned DNAs, the genomes of HPV-1a, HPV-2a, and HPV-4 were analyzed for nucleotide sequence homology. Under standard hybridization conditions (Tm = --28 degrees C), no homology was detectable among the genomes of these papilloma viruses, in agreement with previous reports. However, under less stringent conditions (i.e., Tm = --50 degrees C), stable DNA hybrids could be detected between these viral DNAs, indicating homologous segments in the genomes with approximately 30% base mismatch. By using specific DNA fragments immobilized on nitrocellulose filters, these regions of homology were mapped. Hybridization experiments between radiolabeled bovine papilloma virus type 1 (BPV-1) DNA and the unlabeled HPV-1a, HPV-2a, or HPV-4 DNA restriction fragments under low-stringency conditions indicated that the regions of homology among the HPV DNAs are also conserved in the BPV-1 genome with approximately the same degree of base mismatch.